Infecções parasitárias do apêndice cecal e suas relações com apendicite aguda - Da Silva, Danielle Fernandes [UNESP]; Da Silva, Reinaldo José [UNESP]; Da Silva, Márcia Guimarães [UNESP]; Sartorelli, Alesso Cervantes [UNESP]; Takegawa, Bonifácio Katsunori [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (My University, 2008)
From 1,600 surgically removed appendices, 24 (1.5%) were found to have helminths. Enterobius vermicularis was observed in 23 of the 24 specimens (95.8%) and Taenia sp was detected in only 1 (4.2%) case. Sixteen patients (66.7%) were less than 10 year-old; 15 patients were male and 9 female. Pathologic analysis disclosed acute neutrophilic inflammation in 12 cases and lymphoid hyperplasia in 10 of the 24 appendices. Gangrenous appendicitis was diagnosed in 3 cases and peritonitis was found in 11 of the 24 infested appendices. Parasitic infection of the appendix is an uncommon cause of acute appendicitis in children and adolescents.
Parasitic infection of the appendix and its possible relationship to acute appendicitis
Keywords: Appendicitis; Appendix; Cecal diseases; Parasitic diseases